2007
DOI: 10.1038/sj.ejcn.1602855
|View full text |Cite
|
Sign up to set email alerts
|

Continuity and stability of eating behaviour traits in children

Abstract: Objective: To discover whether eating behaviour traits show continuity and stability over childhood. Subjects/Methods: Mothers of 428 twin children from the Twins Early Development Study participated in a study of eating and weight in 1999 when the children were 4 years old. Families were contacted again in 2006 when the children were aged 10 years, with complete data on 322 children; a response rate of 75%. At both times, mothers completed the Child Eating Behaviour Questionnaire (CEBQ) for each child. Contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
259
5
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(315 citation statements)
references
References 37 publications
22
259
5
11
Order By: Relevance
“…A number of studies in childhood have found relationships between child eating behaviour and overweight or adiposity (26)(27)(28)(29) , but these were not prospective, making it difficult to distinguish cause and effect. One study has shown that child eating behaviours track through mid childhood (30) . Recent work in this area has suggested that childhood eating behaviours associated with adiposity are quite strongly heritable (31) and thus one might expect that there would be behavioural associations with adiposity present at the earliest age.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies in childhood have found relationships between child eating behaviour and overweight or adiposity (26)(27)(28)(29) , but these were not prospective, making it difficult to distinguish cause and effect. One study has shown that child eating behaviours track through mid childhood (30) . Recent work in this area has suggested that childhood eating behaviours associated with adiposity are quite strongly heritable (31) and thus one might expect that there would be behavioural associations with adiposity present at the earliest age.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence on heritability and tracking of certain eating behaviours. 32,33 Hence, assessing eating behaviour by a short questionnaire could be useful in child health care to identify normal weight children with a susceptibility to overeating and weight gain, and who therefore would benefit most from dietary counselling. Such effective intervention approaches targeted towards children are needed.…”
Section: Discussionmentioning
confidence: 99%
“…This is important because research has shown that children's eating behaviours and parental feeding practices are relatively stable from infancy into later childhood. 33,34 Examining cultural differences in the stability and continuity of both eating behaviours and parental feeding practices is also an important area for further work.…”
Section: Discussionmentioning
confidence: 99%